Character of iron deficiency in patients with anemia of different degrees of severity, developed against the background of chronic heart failure - A. N. Belovol; P. G. Kravchun; N. G. Ryndina (Zaporožskij Medicinskij Žurnal)
The study involved 145 patients with chronic heart failure. The study group included 87 anemic patients with chronic heart failure. The comparison group consisted of 58 patients with chronic heart failure without anemia. The presence of 1st grade anemia, developed on the background of chronic heart failure, is characterized by the presence of functional iron deficiency. The increasing of anemia severity associated with the appearance of a patients cohort with absolute iron deficiency.